Detection of Mango Tree Varieties Based on Image Processing - Eko Prasetyo (Universitas Pendidikan Indonesia, 2016)
Mango is one of the most favourite fruits in the world. Therefore, this type of fruit has been researched deeply to enrich the variety. Here, the purpose of this study was to find the easiest method to determine the type and the variety of mango. In short of the experimental method, we analyzed the leaf using an image processing method. To confirm our result, several analyses were also conducted: leaves process digital image acquisition, and preprocessing, as well as feature extraction and classification. The result showed that our image processing method was effective to detect the variation of up to 78%. We believe that further study using this method will be effective for other types of fruits.